Алгоритм встановлення джерел розподіленої генерації в електричних мережах - Жильцов, А.В.; Бодунов, В.М.; Гай, О.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
The distributed generation sources must not adversely affect the quality and reliability of electricity supplied to other customers on the network, so the complex analysis of the mode of electrical power system is needed. Algorithm of connection of the distributed generation source in electrical power systems is offered in article.